How to approach the 17 SDGs in a practical and interdisciplinary way: an extension action (Citizenship in Action: Extension and Culture Magazine, 2024)
How to approach the 17 SDGs (Sustainable Development Goals) in a practical and interdisciplinary way was an extension action, in the format of an EAD course, developed and offered by a student of a specialization course at the Federal Institute of Santa Catarina. The extensionist action is optional in the Specialization in Technologies for Professional Education course and to participate, the student presents a project. In the case of this report, it is an EAD training course for high school teachers, addressing the use of the 17 SDGs in the classroom, with digital technologies. The course's premise was to contextualize, understand and apply in practice the discussion about the progress of actions to meet sustainable goals in Brazil, and the importance of working on the theme in an interdisciplinary way, using digital tools and in the distance learning format. Most of the workload was asynchronous, with a synchronous activity, via Webconference, for setting up and evaluating the course. 40 vacancies were offered, with 32 enrolled and 20 effective participants, certified at the end. The participants considered that the course met expectations, and also pointed out that the practices suggested in the course are feasible in a face-to-face school environment and in distance learning courses. Didactic resources whose content deals with the SDGs were experimented, using free access digital tools such as videos, games, and the production of didactic material, providing a new look at the use of these tools, little used in pedagogical practice.
Keywords: SDGs; high school; education; teacher training